EFEKTIVITAS PELAKSANAAN SUPERVISI OLEH PENGAWAS DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU IPA PADA SMP NEGERI 3 INGIN JAYA KABUPATEN ACEH BESAR - Nurmala .; Murniati AR; Bahrun . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
One of the principal's role is to improve the educator professional and the quality of education in the educational institution through the implementation of supervision. This study aims to determine the process of supervisory program preparation, the techniques applied, the implementation of supervision/evaluation conducted and the feedback conducted by supervisors in improving the professional educator through supervision at SMP Negeri 3 Ingin Jaya Aceh Besar District. This research uses qualitative descriptive method and data collection using interview technique, observation, and documentation. The subjects of this study were school supervisors, principals and educators of science subjects. The results of this study indicate: (1) preparation of supervisory program involves all supervisors in Aceh Besar District through stages consisting of annual program, semester program and academic supervision plan (RPA); (2) the techniques applied in the implementation of supervision are individual techniques and group techniques; (3) evaluation of the implementation is carried out after the supervision process takes place and made the data for the supervisor to be collected to know the achievement of the targets that have been set, in order to be followed up with the next coaching program; (4) providing feedback by supervisors orally is to provide comments on the observation of the learning process and the provision of comments in writing to the results of observations of the learning process and followed by Action Plan of strengthening and reward for educators who have reached the standard, educators who have not reached the standard given educational direction and provide opportunities for educators to attend further training or upgrading.